Deaths and disability-adjusted life years burden attributed to air pollution in China, 1990–2019: Results from the global burden of disease study 2019 - Gan, Hui; Cheng, Long; Zhai, Yingying; Wang, Yimin; Hu, Haisheng; Zhu, Zheng; Sun, Baoqing (Frontiers in Environmental Science, 2022)
Background: The impact of deaths and disability-adjusted life years (DALYs) caused by air pollution in China has not been well elucidated. We aimed to analyze the association of air pollution with deaths and DALYs in the Chinese population. Methods: We extracted data on burden due to deaths and disability-adjusted life years attributed to air pollution in the previous 30 years in China from the Global Burden of Disease (GBD) study 2019 and performed a comprehensive analysis and summary. Results: 1.85 (95% UI: 1.57–2.17) million Chinese people lost their lives as a result of air pollution in 2019, a slight decrease from 1990. In 2019, the disability-adjusted life years (DALYs) caused by air pollution in China was 42.51 (95% UI: 36.34–49.48) million, a 30.2% decrease from 1990. From 1990 to 2019, both age-standardized death rate (ASDR) and age-standardized DALYs due to air pollution in China showed a significant year-on-year downward trend. Air pollution–related deaths and DALYs occurred mostly in people over the age of 50 years. Stroke, ischemic heart disease, and chronic obstructive pulmonary disease were attributed the maximum death burden due to air pollution in China in 2019. Conclusion: Over the past 30 years, air pollution has brought a heavy disease burden to China, and in the future, joint efforts are required to improve the air quality.